ACCOUNTING EDUCATION, DISCIPLINE, AND SUPERVISION WHEN WOMEN IN CHARGE IN ISLAMIC MICROFINANCE: CASE STUDIES OF INDONESIA AND PAKISTAN - Mukhlisin, Murniati; Tamanni, Luqyan (Journal of Islamic Monetary Economics and Finance, 2025)
This paper investigates the relations between women's freedom within the family and their access to accounting education, adherence to discipline, and supervision for the cases of Indonesia and Pakistan using the Structural Equation modelling. The participation of women in microfinance is deemed crucial for the success of poverty alleviation programs, particularly in countries where group-based initiatives are prevalent. The observation reveals that women involved in Islamic microfinance programs experience economic, moral, and religious empowerment, enabling them to overcome economic challenges and poverty, thereby enhancing their living standards. The findings indicate that women's ability to manage family finances has a direct impact on their access to accounting education, discipline, and supervision. The argument posits that autonomy plays a significant role in influencing accounting education, discipline, and supervision within the observed groups in Indonesia and Pakistan. The study further documents that the influence of women's life freedom in Baitut Tamkin Tazkia Madani (BTTM) Indonesia on accounting education and supervision surpasses that in Akhuwat Pakistan. Conversely, the impact of women's life freedom in BTTM on accounting discipline is lower than that in Akhuwat. This research addresses the existing gap in the literature concerning the study of women and Islamic microfinance, emphasizing the importance of considering Islamic perspectives on women, family, and microfinance in social policies aimed at poverty eradication.ACKNOWLEDGMENTThe authors gratefully acknowledge the partial support of the Ministry of Religious Affairs of the Republic of Indonesia, as well as the research support provided by BTTM (Bogor, Indonesia) and Akhuwat (Lahore, Pakistan). We also express our sincere appreciation to the journal’s editors and anonymous reviewers for their constructive comments and valuable suggestions.